Driving sustainable competitiveness: unveiling the nexus of green intellectual capital and environmental regulations on greening SME performance - Sohu, Jan Muhammad; Hongyun, Tian; Junejo, Ikramuddin; Akhtar, Sadaf; Ejaz, Faisal; Dunay, Anna; Hossain, Md Billal (Frontiers in Environmental Science, 2024)
Within the evolving landscape of contemporary business, where sustainability and innovation intertwine, our study explores into a strategic gap, presenting the rationale behind choosing green intellectual capital (GIC), absorptive capacity (AC), green innovation (GI), environmental regulations (ER), and competitive advantage (CA) as main constructs. This model investigates the complex nature of the competitive landscape of SMEs within the vibrant manufacturing sector using the latest version of SmartPLS 4 for analyzing the complex data. Drawing upon the theory of the natural resource-based view (NRBV), this study uncovers that GIC advances GI and AC, driving SMEs towards sustainable CA, particularly within the context of ER. These findings propose vital insights for SMEs looking to leverage their valuable resource contributing for greening operations and reaching sustainable competitiveness, while also adding contribution to the theoretical developments in understanding resource-based perceptions on greening the manufacturing SMEs. Findings reveal the significant impact of GIC on AC and GI, and their subsequent impact on CA. Furthermore, ER uncovers the essential role in shaping the link between GIC and AC, thus enhancing SMEs' capacity to achieve sustainable competitiveness. This study discloses how SMEs utilize GIC to identify the ER and achieve CA and how NRBV develop understanding of SMEs utilizing their unique resource endowments to drive GI and achieve CA. This study examines the mediating role of AC and GI in this relationship.